Outcome and complications of percutaneous nephrolithotomy for renal stones – Our institutional experience - Rajkumar Ramakrishnan,; Senthil Kumar Poovathai,; Rajasekar Sundaram,; Gopu Rakesh Vamsi,; Sammohit Gulakavarapu,; Vinayak Sangreshi, (Asian Journal of Medical Sciences, 2023)
Background: Percutaneous nephrolithotomy (PCNL) is the preferred treatment of choice for renal calculi. PCNL has evolved remarkably since the eighties when it was first described. PCNL is the treatment of choice for renal stones ≥2 cm. Aims and Objectives: Our aim is to observe the various surgical outcomes of different types of PCNL. Materials and Methods: It is an observational study conducted in our institute a total of 160 pts of renal stone disease who presented to the outpatient department were included in the study. All patients underwent PCNL either in supine or prone position. The parameters such as stone free rate, body mass index (BMI), stone size, operative time, length of stay (LOS), in hospital, and complications were observed. Results: There were no significant differences in stone size between supine and prone PCNL patients. The supine group had a higher mean BMI, shorter mean surgical time, shorter mean LOS, and higher stone free rate. Prone PCNL patients had a higher rate of overall complications. Conclusion: PCNL is one of the best modalities for renal stones management, with supine and modified supine PCNL demonstrating better results in obese patients, and may be considered by all surgeons performing PCNLs.